PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN BUDAYA SEKOLAH TERHADAP KINERJA GURU BERDAMPAK PADA HASIL BELAJAR SISWA - Ade Prayoga (Universitas Majalengka, 2020)
The progress of a nation is very dependent on human resources (HR). Education plays a very important role in the process of improving human resources and education is a major factor in the formation of a qualified human person to face competition entering the era of globalization which is very competitive both in the field of education and technology, so the need for change and development in the world of education. This study aims to find out analyzing descriptively and verification of aspects of leadership, school culture and teacher performance. This research method is a quantitative research method with descriptive and verification analysis techniques. Descriptive method using the calculation of frequency distribution, scoring and average value, while the verification method using path analysis. The sampling technique was taken by cluster proportional random sampling. Descriptive research results indicate that the principal's leadership, school culture, teacher performance and quality of student learning outcomes are in the good category. The results of the verification study prove that leadership and culture have a very positive and significant influence on teacher performance either partially or simultaneously. Teacher performance has a positive and significant effect on the quality of student learning outcomes